Acoustic-electroelastic interactions in ultrasound energy transfer systems: Reduced-order modeling and experiment. (9th June 2020) - Meesala, Vamsi C.; Ragab, Saad; Hajj, Muhammad R.; Shahab, Shima
Abstract: Contactless ultrasound energy transfer from a piezoelectric cylinder or disk subjected to forced vibrations to a piezoelectric receiver offers the capability of safely transferring energy to sensors and devices, which is of great interest in different applications. Physical processes supporting ultrasonic energy transfer include piezoelectric-generated vibrations at a transmitting element, piezoelectric transduction of elastic vibrations at a receiving element, acoustic wave propagation, and acoustic-structure interactions at the surfaces of the transmitting and receiving elements. Considering these processes, we present an experimentally-validated multi-physics model that fills a knowledge gap in terms of accurately representing the fluid-loaded response of piezoelectric disks, usually used in ultrasonic energy transfer as a cylindrical transmitting source-cylindrical receiver combination. First, we derive the governing equations using the generalized Hamilton's principle and solve them using the finite element method. Second, we compute the surface pressure distribution due to acoustic-structure interactions under resonance conditions. We then use the mode shapes and surface pressure distributions obtained from the finite element model in conjunction with the matrix governing equations to develop a reduced-order model with quantified reactive and resistive parts of the acoustic radiation impedance. The developed reduced-order model is then experimentally validated by comparing the electrical impedance of four different piezoelectric disks having various aspect ratios. We also discuss how the proposed approach should be utilized to develop reduced-order model for piezoelectric receivers. The presented approach and reduced-order model allow for accurate identification of critical parameters that govern acoustic energy transfer between piezoelectric disks, which is crucial for designing efficient ultrasonic acoustic energy transfer systems.